New citrus tristeza virus strains (Closterovirus tristezae) detected in the Chlef Valley, Algeria - BENTURQUIA, Abdellah Nabil; MEZIANE, Malika; DJELOUAH, Khaled; ALI-AROUS, Samir (Phytopathologia Mediterranea, 2026)
rus production is economically important in the Chlef Valley, Algeria, but faces several challenges from diseases that threaten yields, fruit quality, and long-term sustainability of orchards. During recent decades, several citrus orchards have shown decline and severe symptoms, mostly associated with tristeza and caused by the virulent VT strain reported in 2019. To update current distribution and strains of tristeza pathogens and potential aphid vectors, an additional survey was conducted in the Chlef Valley from 2021 to 2024. Samples collected from different citrus areas were serologically assessed, showing an increase in the infection rates from 3.2% in 2019 to 4.24% in 2024. The molecular genotype characterization using strain specific RT-PCRs confirmed the presence of the pre-existing T30 and VT genotypes, and two new strains, S1 and T3, were also detected. This study has confirmed the widespread dissemination of the virulent VT genotype of CTV, and has detected additional CTV strains. Discovery of new strains and the further spread of the severe VT genotype, combined with detection of the aphid vector Aphis gossypii Glover, poses significant threats to the citrus industry in Algeria. This situation requires proactive measures by the National Phytosanitary Services, including extending surveillance to other citrus Algerian production regions.